2010
DOI: 10.1186/1476-7961-8-14
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of two histamine-metabolizing enzymes genes and childhood allergic asthma: a case control study

Abstract: BackgroundHistamine-metabolizing enzymes (N-methyltransferase and amiloride binding protein 1) are responsible for histamine degradation, a biogenic amine involved in allergic inflammation. Genetic variants of HNMT and ABP1 genes were found to be associated with altered enzyme activity. We hypothesized that alleles leading to decreased enzyme activity and, therefore, decreased inactivation of histamine may be responsible for altered susceptibility to asthma.MethodsThe aim of this study was to analyze polymorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
1
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 21 publications
1
20
1
1
Order By: Relevance
“…SNP in the HNMT gene, but not in ABP1 , significantly influenced the risk of asthma in a Polish population [18]. Polymorphisms in the HDC and SLC22A3 genes influenced the risk of both rhinitis and asthma [19].…”
Section: Discussionmentioning
confidence: 99%
“…SNP in the HNMT gene, but not in ABP1 , significantly influenced the risk of asthma in a Polish population [18]. Polymorphisms in the HDC and SLC22A3 genes influenced the risk of both rhinitis and asthma [19].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the 2002 GINA guidelines, asthma severity was categorised as mild, moderate or severe o6 months before inclusion in the study. Atopy was defined according to previously described criteria [8].…”
mentioning
confidence: 99%
“…for HNMT 314 occurred more frequently among Caucasian asthmatic children when compared to healthy controls [43]. Conflicting reports exist among various ethnic groups and asthma phenotypes in relation to the HNMT 314 SNP and asthma [36,37,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Although the functional significance of many of these SNPs is unknown, several studies have been conducted to explore potential associations between histamine related genes and asthma and allergic disease [6,17,[33][34][35][36][37][38][39][40][41][42][43]. We have previously reported that the HRH1 gene was more highly expressed in buccal tissue from those with asthma compared to those without asthma [44].…”
Section: Introductionmentioning
confidence: 99%